Multiple shoot regeneration and effect of sugars on growth and nitidine accumulation in shoot cultures of Toddalia asiatica - Praveena, Chinthala (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Toddalia asiatica (Rutaceae) is an important medicinal plant in traditional medicinal system of India and China. Nitidine production from callus cultures of the plant had been investigated, but in vitro multiplication and secondary metabolite production from shoot cultures is not reported. OBJECTIVE: The aim of the present work is to establish protocol for in vitro multiple shoot regeneration of T. asiatica and to investigate the secondary metabolite, nitidine production from the shoot cultures. MATERIALS AND METHODS: Different explants were used for shoot regeneration on MS supplemented with benzyl adenine (BA) either alone or in combination with naphthalene acetic acid (NAA) in different combinations. Effect of different sugars and different concentrations of sucrose on biomass accumulation in shoot cultures in liquid medium was investigated. For in vitro rooting, shoots culture were inoculated to half strength MS medium supplemented with different concentrations of indole butyric acid. Quantitative analysis of shoot culture extracts was done for estimation of nitidine by HPTLC. RESULTS: Shoot cultures were successfully initiated and established from nodal and shoot tip explants on MS medium supplemented with benzyl adenine and sucrose (3% w/v). Sucrose at a concentration of 3 % w/v was found to be optimum for growth and biomass accumulation. In vitro rooting of shoots was achieved on half strength MS medium supplemented with indole butyric acid 3 mg/l. Investigation of secondary metabolite production ability of the in vitro regenerated shoot cultures revealed their ability to biosynthesize nitidine. CONCLUSION: Shoot cultures were established and nitidine production has been observed.